Hubungan Dismenore Primer Dengan Aktivitas Belajar Siswi SMK Bina Putra Nugraha Kadupandak Cianjur Jawa Barat Tahun 2023 - Selvina Widianti; Irma Herliana; Saiful Gunardi (Pusat riset dan Inovasi Nasional, 2024)
Primary dysmenorrhea is menstrual pain that is not based on a pathological condition. Female students who experience primary dysmenorrhea will certainly feel that their learning activities are disrupted, and this often results in them being absent or unable to attend school. This research aims to determine the relationship between primary dysmenorrhea and the learning activities of female students at SMK Bina Putra Nugraha Kadupandak Cianjur, West Java in 2023. The type of research is quantitative with a cross sectional design. The population is all 38 female students of Bina Putra Nugraha Vocational School. The sampling technique uses nonprobability sampling with a total sampling technique. The data analysis used was univariate and bivariate using the Spearman's Rank Correlation Coefficient test. Based on data analysis, the results obtained were from 38 respondents, the largest distribution of respondents were female students who experienced moderate pain during menstruation, namely with a frequency of 23 respondents (60.5%), and mild pain with 15 respondents (39.5%). while the results of learning activities showed that the majority of respondents were female students whose learning activities were disrupted due to the impacts caused by primary dysmenorrhea with a frequency of 33 respondents (86.8%) being disturbed. From the results of the Spearman rank correlation test, it can be seen that the value of p = 0.003 (p < 0.05). The results of the correlation coefficient show that there is a relationship between primary dysmenorrhea and the learning activities of female students at SMK Bina Putra Nugraha Kadupandak Cianjur, West Java in 2023. Therefore, the proposed hypothesis means that Ho is rejected and Ha is accepted.